Nomenclature and revised typification of Cheilanthes bonariensis (Cheilantheae, Pteriedaceae) - Ponce, Marta Monica (2011)
A revised typification of Acrostichum bonariense, based on the cited illustration, is necessary. An epitype is designated to interpret the inadequate original drawing.